Potential novel therapeutic strategies from understanding adipocyte transdifferentiation mechanisms. Issue 2 (March 2015) - Sartini, Loris; Frontini, Andrea
<x xml:space="preserve">Abstract</x> Brown adipocytes are located in discrete anatomical locations in both small mammals and in humans. 'Brown-like' adipocytes, also known as brite (brown in white) or beige adipocytes are found interspersed among white adipocytes in several fat depots. From a functional point of view, the activity of brown and brite cells is similar, that is, heat production mediated by uncoupling protein 1. The morphology and expression of 'thermogenic' genes is also very similar in these two cell types. The origin of brite adipocytes is under intense investigation because enhancing their presence and activity has the potential to promote a healthy metabolic profile. Transdifferentiation mechanisms as well as de novo recruitment have been investigated. The characterization of the mechanisms involved in the recruitment and activation of brown/brite adipocytes in adult humans, could open the avenue for promising therapeutic strategies to curb metabolic diseases.